Importance of laboratory experimental studies of silicate grains for exoplanet atmosphere characterization - Potapov, Alexey; Bouwman, Jeroen (Frontiers in Astronomy and Space Sciences, 2022)
The study of exoplanetary atmospheres extends the frontiers of astronomy, astrophysics, and astrochemistry. Moreover, studies of exoplanets as being linked to the search for extraterrestrial life and other habitable planets are of interest not only for scientists, but for a much wider public audience. There is much evidence that clouds exist and are common in the exoplanetary atmospheres at high temperatures. Their origin can be gas-phase condensation of silicate materials and other refractory materials. Clouds have a major impact on the planets’ observable properties. Models describing atmospheres of exoplanets and brown dwarfs point to the necessity of including nanometer- to micrometer-sized grains of silicates. Observational mid-IR spectra have also provided tentative evidence of silicate grain absorption. Thus, silicates seem to be the first target for future astronomical observations of cloudy atmospheres and for laboratory studies supporting these observations. However, high-temperature laboratory studies of optical and structural properties of refractory materials, including silicates, and of gas-grain and grain surface chemistry needed for the decoding of astronomical spectra and for the development of reliable atmospheric models present practically uncharted territory. The aim of our paper is to review previous studies of optical and chemical properties of silicate materials and to emphasize the importance and perspective of high-temperature measurements of laboratory analogues of atmospheric silicate grains for exoplanet atmosphere characterization. This is particularly important in the light of new advanced astronomical instruments, which, as we expect, will bring comprehensive information on exoplanetary atmospheres.